2015
DOI: 10.1017/s0144686x15000987
|View full text |Cite
|
Sign up to set email alerts
|

Exit, voice and indifference – older people as consumers of Swedish home care services

Abstract: Sweden has in the last 20 years undergone an extensive process of marketisation of its home care sector. Where the public sector once was the only provider of home care services, there is now a wide array of different, private alternatives for older people to choose from, using their publicly funded voucher. The publicly funded home care services in Sweden are, in other words, to a large extent organised according to the principles of a quasi-market. Older people with care needs are therefore now considered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 9 publications
4
18
0
1
Order By: Relevance
“…An analysis of the information from providers showed that it provided little guidance for users to make informed choices (Moberg, Blomqvist & Winblad, 2016). Many older people do not see the value of choosing between different, more or less anonymous, service providing agencies and very few change their initial choice of provider of eldercare (Edebalk & Svensson, 2010;National Board of Health and Welfare, 2015;Vamstad, 2016). However, other findings have suggested that older people, especially those with higher income and educational levels, appreciate the opportunity to choose the provider of their care and services (Hjalmarsson & Norman, 2004;Vamstad, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the information from providers showed that it provided little guidance for users to make informed choices (Moberg, Blomqvist & Winblad, 2016). Many older people do not see the value of choosing between different, more or less anonymous, service providing agencies and very few change their initial choice of provider of eldercare (Edebalk & Svensson, 2010;National Board of Health and Welfare, 2015;Vamstad, 2016). However, other findings have suggested that older people, especially those with higher income and educational levels, appreciate the opportunity to choose the provider of their care and services (Hjalmarsson & Norman, 2004;Vamstad, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many older people do not see the value of choosing between different, more or less anonymous, service providing agencies and very few change their initial choice of provider of eldercare (Edebalk & Svensson, 2010;National Board of Health and Welfare, 2015;Vamstad, 2016). However, other findings have suggested that older people, especially those with higher income and educational levels, appreciate the opportunity to choose the provider of their care and services (Hjalmarsson & Norman, 2004;Vamstad, 2016). In a recent study of older users of Swedish home care services with Free Choice Systems, 13% claimed that they did not know that they could choose their provider, and almost 25% reported that the municipal authorities in fact had made the choice (Vamstad, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they are rarely trained to work with older people to ensure that they can increase control of their own health. In Sweden, as in many countries, "ageing in place is the current policy, de ined as remaining in the community with some level of independence, autonomy and connection to social supports including family and friends [27][28][29]. It also avoids costly institutional care.…”
Section: Discussionmentioning
confidence: 99%
“…Siksi aito valinnanvapauden toteutuminen ja asiakkaiden mahdollisuus äänestää jaloillaan voi sopia huonosti palveluasumisen kaltaisiin palveluihin (Rostgaard 2006). Tutkimustietoa palveluntuottajan vaihtamisesta vanhuspalveluissa on jo Ruotsista, missä vanhusten kotipalvelut on jär-jestetty asiakkaan vapaalla valinnalla (Vamstad 2015). Tutkimuksen mukaan vanhukset eivät vaihtaneet palveluntuottajaa lähes lainkaan, ja osa heistä ei edes ollut tietoisia siitä, että he olivat tehneet valinnan palveluntuottajien välillä.…”
Section: Et Tää Palveluseteliajatus Perustuu Siihen Ettäunclassified